a)
to solve a, the following rules are crucial:
(i) [tex]log_ab-log_ac=log_a \frac{b}{c} [/tex]
so the difference of 2 logarithms with the same base, is the logarithm of their division, preserving the same base.
(ii) if [tex]log_ab=log_ac[/tex] then b=c.
so if 2 logarithms with the same base are equal, then the arguments (b and c) are equal as well.
so
[tex]log_3xy-log_3(x-1)=log_36 x^{2} -1[/tex]
apply rule (i):
[tex]log_3 \frac{xy}{x-1}=log_3(6 x^{2} -1)[/tex]
apply rule (ii):
[tex] \frac{xy}{x-1}=6 x^{2} -1[/tex]
now 'isolate' y:
[tex]y=(6 x^{2} -1) \frac{(x-1)}{x} [/tex]
b)
some more rules:
(iii) [tex]log_x a^{n}=nlog_x a[/tex]
(iv) [tex]log_a b= \frac{1}{log_b a} [/tex]
apply iii and iv:
[tex]log_x25=log_x 5^{2}=2log_x 5=2 \frac{1}{log_5 x}=\frac{2}{log_5 x}[/tex]
then substitute [tex]log_5 x=u[/tex] in the equation:
[tex]2u=5- \frac{2}{u} [/tex]
[tex]2u=\frac{5u-2}{u} [/tex]
[tex]2u^{2}=5u-2 [/tex]
[tex]2u^{2}-5u+2=0[/tex]
so now we have a quadratic equation of degree 2,
a=2, b=-5, c=2
the discriminant is [tex] b^{2}-4ac=25-16=9[/tex], the root of it is 3
so the roots are:
[tex]u_1= \frac{-b+3}{2a}= \frac{5+3}{2*2}= \frac{8}{4} =2[/tex]
and
[tex]u_2= \frac{-b-3}{2a}= \frac{5-3}{2*2}= \frac{2}{4} = \frac{1}{2} [/tex]
finally, we convert u's to x's:
[tex]log_5 x=u[/tex] means [tex] x=u^{2} [/tex]
so for u=2, x=4, and for u=1/2 we have x=1/4
Answers:
A) y=(6 x^{2} -1) \frac{(x-1)}{x}
B) solution set: {4, 1/4}